Endovascular and Clinical Outcomes of Vertebrobasilar Intracranial Atherosclerosis-Related Large Vessel Occlusion - Baek, Jang-Hyun; Kim, Byung Moon; Heo, Ji Hoe; Kim, Dong Joon; Nam, Hyo Suk; Kim, Young Dae (Frontiers in Neurology, 2019)
Background and Purpose: Endovascular treatment (EVT) for acute vertebrobasilar intracranial atherosclerosis-related large vessel occlusion (ICAS-LVO) and its outcomes are not well known. We aimed to evaluate endovascular and clinical outcomes of vertebrobasilar ICAS-LVO patients who underwent EVT. Methods: Consecutive acute stroke patients who underwent EVT for vertebrobasilar LVO were retrospectively reviewed. Patients were assigned to the ICAS (+) or the ICAS (–) group based on angiographical findings. Procedural details and clinical outcomes were compared between the ICAS (+) and ICAS (–) groups. Results: This study included 77 patients with acute vertebrobasilar LVO who underwent EVT. Among the study subjects, 24 (31.2%) had an ICAS-LVO. Recanalization was achieved in 19 patients in the ICAS (+) group (79.2%), which was comparable with the ICAS (–) group (84.9%; p = 0.529). However, recanalization using conventional endovascular modalities (stent retriever thrombectomy, contact aspiration thrombectomy, or intra-arterial urokinase infusion) was less successful in the ICAS (+) group (36.8%) than the ICAS (–) group (100.0%; p < 0.001). All the remaining patients in the ICAS (+) group required specific rescue treatments appropriate for ICAS, including balloon angioplasty, stenting, or intra-arterial glycoprotein IIb/IIIa inhibitor infusion to obtain a successful recanalization. Procedural time was not significantly longer in the ICAS (+) group. The rates of favorable outcomes (37.5% vs. 41.5%; p = 0.740), death, and symptomatic intracerebral hemorrhage were not significantly different between the groups. Conclusion: ICAS-LVO was common in patients who underwent EVT for acute vertebrobasilar LVO. Although conventional modalities were often ineffective for vertebrobasilar ICAS-LVO, a comparable recanalization rate could be obtained with ICAS-specific modalities. Recanalization rate and procedural time were comparable, and clinical outcomes did not differ between patients with or without ICAS-LVO.